2020
DOI: 10.1177/0040517520910217
|View full text |Cite
|
Sign up to set email alerts
|

Study of adaptive thermochromic camouflage for combat uniform

Abstract: Adaptive camouflage refers to the adaptation of an object, such as a military vehicle or soldier, to its surroundings. Although the use of camouflage by military forces dates back to the First World War, this research will address the development of an adaptive color changeable system based on selected thermochromic inks following the colors used in Czech woodland and desert combat uniforms. The printed color pattern mimics leaf design, which transforms into desert design based on thermal conditions (hot air a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The work of many researchers demonstrates the importance of wearer comfort, resistance to laundering, and maintaining the functionality of the garment over time [ 14 , 16 , 23 , 31 , 34 , 39 , 40 , 44 ]. There are benefits in avoiding the need for embedded electronics as this adds complexity in terms of washing and powering of devices, especially since energy harvesting capabilities are not ready for use in textile systems yet.…”
Section: Discussion and Path Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of many researchers demonstrates the importance of wearer comfort, resistance to laundering, and maintaining the functionality of the garment over time [ 14 , 16 , 23 , 31 , 34 , 39 , 40 , 44 ]. There are benefits in avoiding the need for embedded electronics as this adds complexity in terms of washing and powering of devices, especially since energy harvesting capabilities are not ready for use in textile systems yet.…”
Section: Discussion and Path Forwardmentioning
confidence: 99%
“…Viková and Pechová examined the camouflage properties of thermochromic inks on two different fabrics, one a plain weave cotton/polyester blend and the other a cotton/polyester blend with a Czech desert camouflage pattern [ 40 ]. Varying concentrations (10–600 g.kg −1 ) of thermochromic inks with transition temperatures ranging between 30 and 39 °C were dissolved with a dye precursor and color developer in a hydrophobic organic solvent, then encapsulated.…”
Section: Existing Technologies Applicable To Visible and Ir Camouflagementioning
confidence: 99%
“…In recent decades, some reports on the stability of thermochromic materials have been carried out. Mojca Friškovec 26 found that ultraviolet rays and temperatures much higher than 150°C would make the thermochromic materials lose color, and the stability been improved by 3–4 times by treatment thermochromic fabrics with commercial UV absorbers 27 . Hironori ODA 28,29 synthesized a series of thermochromic materials with UV absorption functional groups which effectively improve the light resistance of fluorane dye, which confirmed that the anti UV technology is an effective way to improve the light fastness of fluorane dye.…”
Section: Introductionmentioning
confidence: 93%
“…The word thermochromic is the combination of two words: thermos and chromic, where thermos means heat and chromic means colour change. When the chromic materials change colour due to the application of heat such type of fabrics are called thermochromic fabrics [21]. This phenomenon is referred to as thermochromism.…”
Section: Thermochromic Techniquementioning
confidence: 99%